A medida das coisas: japonesidades e parentesco entre associados da Nipo em Araraquara - Hatugai, Érica Rosa (Universidade Federal de São Carlos, 2011)
This research is an anthropological analysis of a Japaneseness developed within some families and their descendants who are part of an associative context of Japanese immigrants in the city of Araraquara, state of São Paulo. The comprehension of this Japaneseness is the result of an ethnography aimed at the constructs which formalized the native category of Japanese and the classifications resulting from it. According to the native knowledge of this category, the social relationships among the families and the individual and collective perceptions of the specificity of "Japanese neither constituted crises nor identity manipulations for the individiduals. The native theories shed light on the awareness of the "japanese" differences which constituted a "Brazilian Japanese" or "Japanese Brazilian" way, and exposed an associative language hinging upon the family and the notions of substances.
Keywords: Antropologia social; Japonesidade; Família; Tradição; Substância (Filosofia); Associativismo; CIENCIAS HUMANAS::ANTROPOLOGIA